The City of Padang Challenges For Paradiplomacy - Rika Isnarti; Sofia Trisni (AEGIS : Journal of International Relations, 2020)
International activities of local governments, also known in the literature as paradiplomacy, have significantly increased in the recent years. In Indonesia, local governments are allowed to conduct international relations or city diplomacy in supporting of central government. In doing so, multiple international agreements have been signed by Indonesian local governments, mostly establishing sister city relations. The most active actors on the international stage are big cities, such as Jakarta, Yogyakarta, and Bandung, all situated in Java. This research aims to explore challenges faced by small city, in this case city of Padang in conducting city diplomacy. The authors interviewed public officers in city of Padang and collected secondary data on the topic based on literature study. this article argues that small city has challenges that are not faced by big cities.  The study found that small city cannot conduct city diplomacy as well as big cities due to the following factors: lack of awareness of city diplomacy, small number of staff with sufficient knowledge about international relations, and lack of information and idea about the implementation of sister city MoU or action plan and complex bureaucracy procedure in conducting an agreement which potentially less motivate staff in doing paradiplomacy. This article concludes that city of Padang is still working to obtain many agreements in term of sister city while creating many action plans to effectively the agreements.